2018
DOI: 10.1016/j.ultrasmedbio.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Tendon Matrix Change Using Ultrasound Imaging: A Systematic Review and Meta-analysis

Abstract: Ultrasound imaging (US) is an accurate and reliable method used to diagnose tendinopathy. This systematic review was aimed at identifying common criteria and parameters used to diagnose tendinopathy, the methodological quality of studies and the predictive value of US. Nineteen studies met the inclusion criteria, with the Achilles, quadriceps and patella tendons being investigated. Overall, there was significant heterogeneity between the criteria used to diagnose tendinopathy utilising US. The methodological q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 79 publications
(290 reference statements)
4
26
0
Order By: Relevance
“…Phase 1: criteria development Following a systematic review, 31 an initial criteria was proposed that incorporated both the continuum model of tendon pathology 9 11 and common parameters used to measure tendinopathy on USI. 31 Additionally, as identified in previous studies, 18 31 34 an ordinal scale was used that included measures of tendon thickness, echogenicity and vascularisation.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Phase 1: criteria development Following a systematic review, 31 an initial criteria was proposed that incorporated both the continuum model of tendon pathology 9 11 and common parameters used to measure tendinopathy on USI. 31 Additionally, as identified in previous studies, 18 31 34 an ordinal scale was used that included measures of tendon thickness, echogenicity and vascularisation.…”
Section: Materials and Methods Study Designmentioning
confidence: 99%
“…31 34 This, in conjunction with the cross-sectional design of many imaging studies, 30 and lack of a clinical gold standard with which to compare images, 29 contributes to the uncertainty of the relevance of USI in the clinical diagnosis of tendinopathy. 30 When assessing current methods for diagnosing tendinopathy using USI-based criteria, a recent systematic review 31 reported that the most common parameters used to measure tendon pathology include tendon thickness, echogenicity and vascularity. Furthermore, while the stages of tendinopathy are distinguished by specific imaging features, 9 11 no studies used the continuum model of tendon pathology to stage tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations